DAMPAK PENYELENGGARAAN PROSES PEMBELAJARAN KOLABORATIF MERDEKA BELAJAR BAGI MAHASISWA INSTITUT TRANSPORTASI DAN LOGISTIK TRISAKTI - Marthaleina Ruminda; Yulianti Keke; Euis Saribanon; Mustika Sari; Indriyati (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to determine the implementation and impact of their collaborative learning process for students at the Trisakti Institute of Transportation and Logistics. This research was conducted on 1,190 students, 92 lecturers, and 20 educators from the Faculty of Management and Business (FMB) of the Trisakti Transportation and Logistics Institute, Jakarta. The results of the study are that the implementation of MBKM has been going well within 1 year, there are several things that need to be improved, related to socialization, communication between all stakeholders involved (Students, Lecturers and Educators) and Students feel the good impact of implementing MBKM, adding additional competencies needed, broaden their horizons and can be a provision after graduation, because of the increase in hard skills and soft skills. So based on the results of students, lecturers, and teaching staff, there are several things that can be improved in the future, namely, first, students, lecturers, and educators still know little about MBKM, so it is necessary to do better socialization. Furthermore, students, lecturers and teaching staff still do not understand the length of learning MBKM, so it is necessary to provide an explanation regarding the length of study for the MBKM program. Then there are quite a lot of students, and lecturers who still don't have the same understanding of MBKM, so it needs to be communicated better. Fourth, it can be seen that students, lecturers and teaching staff feel that MBKM is able to improve soft skills and develop skills as a further provision. Furthermore, the five students felt that the activities were in accordance with the needs of future graduates. Only 3% stated that it was not appropriate and the sixth 55% of Education Personnel felt dissatisfied and did not participate, to increase participation in MBKM implementation, ITL Trisakti needs to socialize and re-communicate this activity. So in the future it is necessary to disseminate information to students, lecturers, and teaching staff regarding MBKM and it is important to continue the ongoing MBKM program in each faculty.